CORRELATION BETWEEN OF SOCIAL SUPPORT WITH SELF CONCEPT ON THE SIDOARJO’S LGBT COMMUNUTY (Research of Sidoarjo’s LGBT Community) - Choirun Nisaa; Asrina Pitayanti; Iva Milia Hani R (STIKES Insan Cendekia Medika Jombang, 2013)
Homosexuality is a sexual orientation that is often difficult to be accepted by the general public because of different sexual orientation pedominantly heterosexual society, this inducing a sense of discrimination and less favorable circumstances. British statistics agency recordered a 90% homosexual population live and work in urban areas of tolerance. Social behaviour unpleasant toward homosexuals impacts that created the conditions in which they don’t received, unappreciated, not recognized, either by family, friends, and society which will make them under pressure. It effects the self-concept homosexual. One of the factors that have an important role in the concept of self homosexual is social support. Social support is definied as a comfort, attention and assistence awards are perceived someone from another person or group. Based on this background, The purpose of this study is to know the effect of the relation of social support to the concept of sel hosexual in Sidoarjo. This research is a type of quantitative. The sample study population consisted of 32 people who had been using of simple random sampling design. The independent variable of this study is social support and the dependent variable of this study is the concept of self homosexual in the LGBT community’s of Sidoarjo.retrival of data using questionaires instrument. While data analysis techniques using Spearman rank test. The result showed that the majoryty of respondens 62,5% have a good social support. And have a positif self concept as much as 71,85%. Spearman rank test of 2 variables are obtained score of ρ = 0.000. The conclusion from this study is that there is a significant relationship between social support and self-concept homosexual. Social support is an important role in the formation of self-concept homosexual.